2019
DOI: 10.1177/1948550619865056
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Marital Satisfaction in Diverse Newlywed Couples

Abstract: Couples’ marital satisfaction is thought to decline over the newlywed years, but recent research indicates that the majority of spouses have high, stable trajectories during this period, and significant declines occur only among initially dissatisfied spouses. These findings are drawn from predominantly White, middle-class samples, however, which may overestimate marital stability compared to samples with higher levels of sociodemographic risk. Accordingly, the current study tested the generalizability of newl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 26 publications
4
34
2
2
Order By: Relevance
“…We found support for our second hypothesis that husbands and wives would have diverging marital experiences during the newlywed years. Unlike prior work, which found low‐income husbands and wives demonstrated a significant decline in satisfaction (Williamson & Lavner, 2019), we found husbands did not report a significant decline in their marital satisfaction. In contrast, for most wives, it appears more difficult to sustain initially high satisfaction, and declines are not concentrated to those with lower initial satisfaction (Proulx et al, 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…We found support for our second hypothesis that husbands and wives would have diverging marital experiences during the newlywed years. Unlike prior work, which found low‐income husbands and wives demonstrated a significant decline in satisfaction (Williamson & Lavner, 2019), we found husbands did not report a significant decline in their marital satisfaction. In contrast, for most wives, it appears more difficult to sustain initially high satisfaction, and declines are not concentrated to those with lower initial satisfaction (Proulx et al, 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…Yet the novelty and exploratory nature of the analyses does not mean the lack of theoretical implications. For example, the estimation of the unconditional growth model is consistent with prior research identifying variability in the developmental trajectories in marital quality across time (Williamson & Lavner, 2020). Those who started with higher happiness and satisfaction experienced few changes across time, whereas those who started with lower happiness and satisfaction became increasingly distressed over time.…”
Section: Limitations and Future Research Directionssupporting
confidence: 81%
“…ER organisations or voluntary sector support organisations could consider relationship training education best practice guidelines suggested in Bakhurst, Loew [ 100 ] and adapt these to ER families experiences. The review, however, found a lack of evidence regarding the prevalence of relationship satisfaction in ER couples which is an important variable to assess long-term relationship trajectories and their relationship with work-stress spillover [ 101 , 102 ]. Finally, the review papers did not assess the sexual dimension of couple relationships and how intimacy and relationships are affected by work burdens, time spent together and distress, hence this is an important factor that should be taken into account with regards to ER relationships and wellbeing [ 103 ].…”
Section: Resultsmentioning
confidence: 99%